Tinjauan Hukum Keluarga Islam Terhadap Problematika Poligami Siri di Kabupaten Tanah Datar - Maratul Husna; Elimartati Elimartati; Nofialdi Nofialdi (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2024)
The primary issues in this thesis are the causes of siri polygamy, the effects it has on siri polygamous families, and how Tanah Datar Regency has dealt with siri polygamy. The purpose of this study is to investigate and elucidate the causes of siri polygamy in Tanah Datar Regency, as well as the effects and solutions related to this phenomenon. The study's findings indicate that: 1) There are frequent arguments between husband and wife, the husband feels capable, and it is customary to follow ancient customs. The second wife-to-be has not processed the previous husband's death certificate. The husband is worried and does not get permission from the first wife. 2) Siri polygamy has negative effects on children, spouses are unjust and insufficient in allocating their income, spouses are uncaring and hardly return home, wives feel betrayed, and marriages are not legally binding in Tanah Datar Regency. 3) Tanah Datar Regency's resolution of siri polygamy, Out of the five data sets, two had amicably (non-litigation) resolved their issues, with both families and the mother present. None of the data sets were settled in court. Regarding unregistered polygamous weddings, the local Nagari administration has not issued any particular regulations. 4) Unregistered polygamous marriages are regarded under Islamic family law as having no legal significance, with the children being entrusted to the mother and the woman having no rights to assert in the event of a divorce or inheritance. Islamic law permits polygamy as long as certain requirements are met, such as the need that it be done properly and with no more than four partners. In addition, the law and KHI stipulate that the woman cannot have children, has an irreversible illness, or is disabled. The husband also needs the consent of the first wife. There is also an assurance that the husband would be able to fairly provide for his wife and kids.